Cultural Flows of Korean Drama in Changing the Orientation of Indonesian Cultural Identity in the Younger Generation - Afifah, Mira Aulia; Firman Aziz; Ryan Ferdiana; Fatimah Azzahra NF; Ronald Yehezkiel Sitompul; Rizqya Aufa Nuraini (PANTUN: Jurnal Ilmiah Seni Budaya, 2025)
Globalization has triggered cross-cultural exchanges across countries, with Indonesia as a multicultural country also experiencing the impact. One significant global phenomenon is the Korean Wave, including the popularity of Korean dramas among Indonesians. Korean dramas are more than just entertainment, they have the potential to influence the cultural identity orientation of the younger generation who are the main consumers. With this, the main focus of the research is to analyze how the impact Korean dramas have on changes in cultural preferences among the younger generation of Indonesia. This research uses an interview method with a qualitative approach. This research involved 5 informants with the criteria of Indonesian young generation aged 18-19 years who actively consume Korean dramas. The results showed that the flow of Korean culture through Korean dramas has the potential to influence the orientation of the cultural identity of the Indonesian people, but the sense of pride and dominance of Indonesian culture still has the potential to be maintained and developed. The contribution of this research lies in its understanding of the interaction between the Korean Wave and the formation of cultural identity among Indonesia's younger generation. The findings show that despite the strong influence of foreign cultures, the younger generation still demonstrates cultural resilience. In addition, this research opens up strategic opportunities for the revitalization of local culture through a more creative and relevant approach to popular media that appeals to young people's tastes.